2016
DOI: 10.7717/peerj.2788
|View full text |Cite
|
Sign up to set email alerts
|

One-year mortality after severe COPD exacerbation in Bulgaria

Abstract: IntroductionOne-year mortality in COPD patients is reported to be between 4% and 43%, depending on the group examined.AimTo examine the one-year mortality in COPD patients after severe exacerbation and the correlation between mortality and patients’ characteristics and comorbidities.MethodsA total of 152 COPD patients hospitalized for severe exacerbation were assessed for vitamin D status, diabetes mellitus (DM), arterial hypertension (AH), and metabolic syndrome (MS). Data were gathered about smoking status a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The 12-month mortality rate was significantly and markedly lower in the DM group (1.9%) than in the UM group (14.2%), the latter of which is consistent with, or lower than, the 12-month mortality rates of 12.5% [28], 16.8% [29], 21% [30] and >23% [31] that have been reported previously for COPD patients following a hospitalisation for an acute exacerbation of COPD. That mortality was lower than expected in the DM group, rather than excessively high in the UM group, suggests that the disease management intervention reduced mortality.…”
Section: Discussionsupporting
confidence: 89%
“…The 12-month mortality rate was significantly and markedly lower in the DM group (1.9%) than in the UM group (14.2%), the latter of which is consistent with, or lower than, the 12-month mortality rates of 12.5% [28], 16.8% [29], 21% [30] and >23% [31] that have been reported previously for COPD patients following a hospitalisation for an acute exacerbation of COPD. That mortality was lower than expected in the DM group, rather than excessively high in the UM group, suggests that the disease management intervention reduced mortality.…”
Section: Discussionsupporting
confidence: 89%
“…Our analyses show that the overall mortality for COPD exacerbation in hospitalized patients was lower than previously reported ranges 37–41 . Studies that reported higher estimates were performed in patients followed up to a year after the index admission, 37,39 while our analyses included only in‐hospital mortality.…”
Section: Discussionmentioning
confidence: 55%
“…Our analyses show that the overall mortality for COPD exacerbation in hospitalized patients was lower than previously reported ranges. [37][38][39][40][41] Studies that reported higher estimates were performed in patients followed up to a year after the index admission, 37,39 while our analyses included only in-hospital mortality. Our analysis also does not include deaths among patients transferred to a skilled nursing facility or intermediate care facility or those who died at home.…”
Section: Discussionmentioning
confidence: 99%
“…Mekov et al discovered that the risk factors for increased mortality were age, FEV 1 values, severe exacerbation in the previous year, and reduced quality of life. 48 Chronic bronchitis increased all-cause mortality and mortality from respiratory causes, cardiovascular diseases, and cancer. 23 In our study, early onset patients had more frequent exacerbation and poorer health status, which could cause death at younger ages.…”
Section: Discussionmentioning
confidence: 99%